Contribution of filtration and photocatalysis to DOM removal and fouling mechanism during in-situ UV-LED photocatalytic ceramic membrane process. (1st November 2022) - Li, Chen; Sun, Wenjun; Lu, Zedong; Ao, Xiuwei; Li, Simiao; Wang, Zhenbei; Qi, Fei; Ismailova, Oksana
Highlights: SRNOM and real water were treatedby in-situ UV-LED photocatalytic ceramic membrane. The contribution of filtration and photocatalysis to DOM removal were identified. UV treatment significantly mitigated membrane fouling, decreasing Rr and Rir . The contribution of DOM removal to fouling mechanism were elucidated. Commercial UV-LED is a suitable UV source for photocatalytic membrane filtration. Abstract: The use of ceramic membranes and ultraviolet light-emitting diodes (UV-LEDs) has advanced the application of photocatalytic membrane for water treatment. We systematically evaluated the contribution of filtration and photocatalysis to dissolved organic matter (DOM) removal and fouling mechanism during in-situ UV-LED photocatalytic ceramic membrane filtration. The results showed that physical rejection primarily led to removal of 4–15 kDa molecules and photocatalysis further increased the removal of 1-4 kDa molecules, causing small sized microbial humic-like or protein-like materials in the permeate. In-situ UV-LED photocatalysis had an excellent effect on membrane fouling mitigation regardless of DOM sources. The dominant fouling mechanism changed from partial blockage to gel layer formation with increasing Ca 2+ concentration but did not change with UV treatment. Correlation analysis revealed that the removal of 1-4 kDa molecules contributed to the mitigation of both reversible and irreversible fouling resistance, and the small molecules were the major cause of irreversible fouling resistance. Removal of 1–4 kDa terrestrial humic acid-like contributed to the pore blockage mechanism for synthetic water. Removal of 4-15 kDa protein-like materials was closely correlated to the pore blockage mechanism for real water. Trihalomethanes (THMs) and haloacetic acids (HAAs) formation potential (FP) were both significantly reduced after photocatalytic ceramic membrane process, but precursors of nitrogenous disinfection by-products (N-DBPs) with high toxicity were not removed by filtration or by photocatalysis, which deserves attention. Membrane rejection made higher contribution to better DBPFP control than photocatalysis. This study provides novel insights into the impact of UV-LED on DOM removal, DBPFP control and fouling mitigation, promoting the development of photocatalytic ceramic membrane filtration. Graphical Abstract: Image, graphical abstract